Chronic Obstructive Pulmonary Disease - A Current Conspectus 2021
DOI: 10.5772/intechopen.95889
|View full text |Cite
|
Sign up to set email alerts
|

Non-Pharmacological Management of Symptoms during Mechanical Ventilation and Chronic Obstructive Pulmonary Disease in Critical Care: Patient Directed Music Listening

Abstract: This chapter provides a review of the literature on nonpharmacological management of symptoms with music listening for critically ill patients during mechanical ventilation and with chronic obstructive pulmonary disease. The critical care environment is high energy, intense, and noisy. These characteristics of the ICU can often exacerbate symptoms and overstimulate patients. Patients may experience increased agitation, anxiety, increased pain or discomfort, and sleep interruptions. Patients are often on variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The aim of this study was to explore the feasibility and acceptability of a patient directed active music making with patients and their families during the BMT process. Music-based interventions are more widely being utilized for patients and their families in various healthcare settings and address challenges related to the treatment process and symptom management [ 56 ]. The results from this feasibility and acceptability study align with findings from music therapy research that indicate it can help address many of the symptoms that patients experience during the BMT process, such as, nausea, fatigue, pain, discomfort, and emotional distress [ 45 , 46 , 47 , 48 , 58 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this study was to explore the feasibility and acceptability of a patient directed active music making with patients and their families during the BMT process. Music-based interventions are more widely being utilized for patients and their families in various healthcare settings and address challenges related to the treatment process and symptom management [ 56 ]. The results from this feasibility and acceptability study align with findings from music therapy research that indicate it can help address many of the symptoms that patients experience during the BMT process, such as, nausea, fatigue, pain, discomfort, and emotional distress [ 45 , 46 , 47 , 48 , 58 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of patient directed music (PDM) interventions empowers patients to exercise their agency in determining what music they want to listen to, when they want to listen to it, and to decide how long they want to listen [ 54 , 55 , 56 , 57 , 58 , 59 ]. Patients initiating music listening showed significantly decreased levels of anxiety and significantly reduced levels of sedative exposure, frequency, and intensity [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…The body of literature surrounding music-based interventions has grown exponentially in the recent years. This is due to numerous factors impacting the use of music-based interventions in research: accessible nature of music (1,2), wide variety of clinical settings in which they are being utilized (1), the myriad of health issues and symptoms being addressed (1)(2)(3), different ways that music is utilized (3)(4)(5)(6)(7), diverse body of disciplines employing and investigating these types of interventions (3), and the increasing amount of research funding dedicated to music intervention research (2). The combination of all these factors, in addition to the growing use of music-based interventions research around the world, necessitate clarity in describing the music-based intervention to understand and consider the unique and specialized needs of patients (1), as well as any cultural implications related to selecting music (2).…”
Section: Introductionmentioning
confidence: 99%
“…These include listening, singing, playing, improvising or composing music (3,6,7). While some of these methods require specialized training and specific equipment to facilitate, some methods are easily accessible and can be self-administered by patients (1,2). A recent narrative and systematic review of reporting music-based interventions indicated that in terminology and content reporting, describing the intervention was inconsistent or misapplied (1,3,44).…”
Section: Introductionmentioning
confidence: 99%